2020
DOI: 10.1371/journal.pone.0227215
|View full text |Cite
|
Sign up to set email alerts
|

A pre-clinical validation plan to evaluate analytical sensitivities of molecular diagnostics such as BD MAX MDR-TB, Xpert MTB/Rif Ultra and FluoroType MTB

Abstract: Rapid diagnosis of tuberculosis (TB) and antibiotic resistances are imperative to initiate effective treatment and to stop transmission of the disease. A new generation of more sensitive, automated molecular TB diagnostic tests has been recently launched giving microbiologists more choice between several assays with the potential to detect resistance markers for rifampicin and isoniazid. In this study, we determined analytical sensitivities as 95% limits of detection (LoD 95 ) for Xpert MTB/Rif Ultra (XP-Ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The tested panel was, however, designed only for relative comparisons and not to provide exact estimates. Despite this limitation, our findings are in line with studies that showed that Xpert MTB/RIF Ultra had a 10-fold-lower LOD than Xpert MTB/RIF, while the LOD of BD Max MDR-TB was equivalent to that of Xpert MTB/RIF Ultra ( 23 , 24 ). Analytical sensitivity may, however, vary in different clinical contexts, and as shown by the current study, a degree of uncertainty remains in predicting clinical performance from analytical data.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The tested panel was, however, designed only for relative comparisons and not to provide exact estimates. Despite this limitation, our findings are in line with studies that showed that Xpert MTB/RIF Ultra had a 10-fold-lower LOD than Xpert MTB/RIF, while the LOD of BD Max MDR-TB was equivalent to that of Xpert MTB/RIF Ultra ( 23 , 24 ). Analytical sensitivity may, however, vary in different clinical contexts, and as shown by the current study, a degree of uncertainty remains in predicting clinical performance from analytical data.…”
Section: Discussionsupporting
confidence: 89%
“…Chakravorty et al, reported an LOD for Xpert of 112.6 cfu/mL(23), which suggests that the quantification of the panel used in our study may be off by one log. The tested panel was, however, Xpert MTB/RIF, while the LOD of BD MAX MDR TB was equivalent to Xpert MTB/RIF Ultra(23,24). Analytical sensitivity may, however, vary in different clinical contexts and as shown by the current study, a degree of uncertainty remains to predict clinical performance from analytical data.…”
mentioning
confidence: 79%
“…In line with this hypothesis, we recently observed an analytical sensitivity of BD MAX of 2.1 cfu/mL with unprocessed sputa being equal to that of Xpert MTB/RIF Ultra. 13 High specificity rates of molecular TB assays are of particular importance in low TB prevalence settings to reach high positive predictive values and to reliably discriminate between MTBC and NTM in smear-positive cases. In this respect, BD MAX seemed to be superior over Abbott RealTime MTB 10,19 and Xpert MTB/RIF Ultra.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a recent validation study, we observed that BD MAX had analytical sensitivity equal to Xpert MTB/RIF Ultra. 13 However, data with clinical, decontaminated, smearnegative respiratory MTBC specimens and nontuberculous mycobacteria (NTM) remain scarce. The goal of the current study was to assess the diagnostic performance and validity of BD MAX by using pre-characterized cohorts of i) MTBC-negative, ii) paucibacillary, and iii) multibacillary MTBC-positive respiratory secretion samples after decontamination using N-acetyl-L-cysteine/sodium hydroxide.…”
mentioning
confidence: 99%
“…Furthermore, the data for Truenat MTB RIF Dx showed similar accuracy to the WHO approved commercial line probe assays indicated by the TAG for centralized DST [GenoType MTBDRplus Version 2.0 (Hain Lifescience, Nehren, Germany) and Nipro NTM+MDRTB detection kit2 (Nipro, Osaka, Japan)] [129,130]. Other systems marketed in 2015-2019 and on the pathway to the WHO evaluation for the centralized determination of molecular resistance to INH and RIF are: Cobas MTB-RIF/INH (Roche, Basel, Switzerland), BD MAX MDR-TB (Becton Dickinson, Sparks, MA, USA), real-time MTB-RIF/INH Resistance assay (Abbott, Abbott Park, IL, USA) and FluoroType MTBDR version 2.0 (RIF, INH) (Hain Lifescience) [129,[131][132][133].…”
Section: Acquired Drug-resistance Of Mtbmentioning
confidence: 99%